Comparison of the Diversity of Weed Types in Oil Palm (Elaeis guineensis Jacq.) Plantations that have not been Replanted and After Replanting in PTPN II North Sumatera - Sari Anggraini; Lisa pebrianti (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
Comparison of the Diversity of Weed Types in Oil Palm (Elaeis guineensis Jacq.) plantations that have not been replanted and after replanting in PTPN II, North Sumatra.